2009
DOI: 10.2353/ajpath.2009.080949
|View full text |Cite
|
Sign up to set email alerts
|

Capillary Defects and Exaggerated Inflammatory Response in the Airways of EphA2-Deficient Mice

Abstract: Both Eph receptors and ephrin ligands have been implicated in blood vessel and neuronal development. Recent studies suggested that EphA2 inhibition reduces tumor angiogenesis, but its role in blood vessel development and inflammation is unclear. We examined these issues using either airways of pathogen-free, EphA2-deficient mice at various ages or EphA2-deficient mice whose airways were inflamed by either Mycoplasma pulmonis infection or ovalbumin sensitization and challenge. EphA2-deficient mice had fewer cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 57 publications
1
37
0
Order By: Relevance
“…Structural studies revealed several sites that are involved in ligand-dependent and ligand-independent EphA2 oligomerization. These sites were found along the extended extracellular domain (ECD), 3 consisting of fibronectin III repeats (FN1 and FN2), ligand-binding domains (LBDs) and cysteine-rich domains, as well as in a cytoplasmic sterile ␣ motif domain situated after the tyrosine kinase domain (TKD) (7,9,10). The functional importance of EphA2 oligomerization via the ECD was confirmed by using site-directed mutagenesis and cellbased signaling assays (7,10).…”
mentioning
confidence: 95%
“…Structural studies revealed several sites that are involved in ligand-dependent and ligand-independent EphA2 oligomerization. These sites were found along the extended extracellular domain (ECD), 3 consisting of fibronectin III repeats (FN1 and FN2), ligand-binding domains (LBDs) and cysteine-rich domains, as well as in a cytoplasmic sterile ␣ motif domain situated after the tyrosine kinase domain (TKD) (7,9,10). The functional importance of EphA2 oligomerization via the ECD was confirmed by using site-directed mutagenesis and cellbased signaling assays (7,10).…”
mentioning
confidence: 95%
“…39 It is well known that initial lymphatics in many tissues 40 -43 including airways 17 do not have a prominent covering of pericytes and basement membrane. Because pericytes and basement membrane are generally believed to stabilize newly formed blood vessels in tumors 44,45 and in inflamed airways, 46 the reason than newly formed lymphatics are resistant to regression despite their lack of pericyte and basement membrane coverage remains unknown. Blood and lymphatic endothelial cells showed distinct reactions to M. pulmonis infection and to dexamethasone treatment, suggesting that the factors responsible for growth and maintenance are distinct from each other.…”
Section: Prevention and Reversal Of M Pulmonis-induced Vessel Changesmentioning
confidence: 99%
“…EphA2 has been reported to regulate interactions between ECs and pericytes. 21 We therefore studied the kidney microvascular responses in EphA2-deficient mice. No differences were found in PTC density and number of myofibroblasts that appear in control and d4 UUO kidneys of WT and EphA2-deficient mice, suggesting minor roles of EphA2 in kidney injury (Supplemental Figure 7).…”
Section: Epha/ephrina Signaling Plays No Role In Kidney Microvascularmentioning
confidence: 99%